Sustainability assessment of public bus transportation sector in westbank, palestine - Fady M A Hassouna (Environmental Research Communications, 2023)
Urban transportation is considered one of the main sources of Greenhouse Gas (GHG) emissions. Therefore, there has been an essential need to develop a sustainable transportation system that could mitigate the environmental impacts by using high-capacity transportations modes, such as public buses. This study has aimed to assess the expected sustainability of the public bus sector in Westbank, Palestine, in case of developing this sector and increasing the number of buses to meet the minimum global requirements (number of buses/1000 population), by developing prediction models for number of buses and passenger cars. Then, the expected reduction in total travelled kilometers by passenger cars has been quantified. After that, the expected reduction in GHG emissions has been determined and the effects on traffic congestion have been investigated. After analyzing the results, the study has concluded that the public bus transport sector in Palestine suffers from the lack of number of buses compared to the number of population, with a value of 0.38 bus/1000 population, which is considered one of the lowest values among the world’s countries. Moreover, by increasing the number of buses to meet the minimum global requirement, there has been a significant expected reduction in CO _2 emissions (94,628.56 ton) compared to the total CO _2 emissions from other sectors in Palestine, and there has been an expected reduction in traffic congestion up to 5.84%.